Art therapy & career counseling : creative strategies for career development across the lifespan - Parker-Bell, Barbara (Barbara Faye); Osborn, Debra S., 1968- (New York : Routledge, Taylor & Francis Group, 2023)
'Art Therapy & Career Counseling is a comprehensive career development guide that offers creative approaches for understanding, assessing, and supporting ethical career development strategies. This book expands on traditional approaches by adding a robust art therapy lens to topics such as career development theories, relational approaches, career resource identification, multicultural concerns, and ethical practices. Additionally, research and practice findings of art therapists, counselors, psychologists, educators, and students are utilized as sources for career-centered art-based strategies. Art therapy educators, art therapists, counselors, and psychologists will appreciate creative approaches to teaching and applying career development through the lifespan'--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Vocational guidance -- Vocational guidance -- United States; Art therapy -- Vocational guidance -- United States; Vocational guidance -- Methodology